An Inquistive Result on DFS Problem of Binary Trees - Justin Sophia, Dr. N. Rama, (International Journal of Scientific Research and Management (IJSRM), 2017)
Let be a complete binary tree of height ,then is called a full binary tree, if all the leaves in T are at level h. Let denote the full binary tree of height .Let denote the time taken by DFS with respect topreorder traversing to find the vertex in the graph . In this paper we analytically compute the for being a full binary tree of height , .